Alternância como pedagogia na Escola Família Agrícola de Ladeirinhas-SE: possibilidades de construção de práticas sustentáveis - Melo, Juliana Franco de (2013)
This thesis consists of a study on the Pedagogy of Alternation as a pedagogical method incorporated to the principles of Field Education, and its contribution to the spreading of ecological agriculture practices, through what was experienced at Escola Família Agrícola de Ladeirinhas (EFAL), located in the town of Japoatã, state of Sergipe, Brazil. EFAL is engaged in the education of young children of rural workers, in different times and places: in social-occupational aspects (family, community, and work) and in educational aspects (students go to boarding schools and have technical education for professional development in farming). By means of a qualitative approach, elements of ethnography grounded in hermeneutical phenomenology were used as a way to interpret the day-to-day experiences observed. This research was categorized as a case study. Data were collected by means of various instruments, such as the observation of classes and practical activities, document analysis, field journal entries, photographic record, and semi-structured interviews with students, school monitors, and the families involved. EFAL is part of regional and national networks which articulate the different Family Centers of Education by Alternation and aim at providing and enhancing the mastering of the required knowledge through alternation, and makes up an educational alternative in rural areas. While analyzing the use of the Pedagogy of Alternation in the dissemination of sustainable principles and practices, it became understood that such method, adapted to the various realities of rural areas, enables individuals to have an integral education. Immersed in territories of inequity intensified by the agribusiness, and affected by policies which encourage the use of unsustainable technology resulting from green revolution packages, EFAs make use of principles and instruments that attempt to reinforce the dialogue between the school world and the life world, between theory and practice. The articulation of the data collected and their analysis made way for critical reflections on the times of school, family, the working of the land, and daily routines, and showed that despite the difficulties in the preparation of monitors and administrators for this differentiated pedagogical method, as well as the necessity of self-financing, there is great potential for it to become a method of integral education, based on the restoring of traditional rural worker knowledge. The articulation between such knowledge and that acquired at EFAL makes it possible for rural citizens to think and act towards sustainable rural development.